2015
DOI: 10.3345/kjp.2015.58.2.60
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between primary headache and constipation in children and adolescents

Abstract: PurposeMany patients presenting with headache also complain of constipation; the relationship between these two symptoms has not been explored in detail. The aim of this study was to investigate the association between primary headache and constipation.MethodsThis retrospective study included all children who attended the Inje University Sanggye Paik Hospital complaining of headache, and who had been followed up for at least 100 days. Patients were divided into 2 groups: group A, in whom the headache improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…However, no such association was found among PWM. Another retrospective study of 96 patients with primary headache also found comorbid constipation in 25%, but this was mostly associated with tension-type headaches[ 56 ]. All studies reported a close correlation of constipation with headache severity, suggesting that it is this factor, together with the related affective and emotional distress, that more adequately explains the association.…”
Section: Other Functional Gi Disordersmentioning
confidence: 99%
“…However, no such association was found among PWM. Another retrospective study of 96 patients with primary headache also found comorbid constipation in 25%, but this was mostly associated with tension-type headaches[ 56 ]. All studies reported a close correlation of constipation with headache severity, suggesting that it is this factor, together with the related affective and emotional distress, that more adequately explains the association.…”
Section: Other Functional Gi Disordersmentioning
confidence: 99%
“…[1] Patients with migraine who were also complaining of constipation were interviewed by a trained researcher (nursing student) based on the Rome III scale to examine their incidence of constipation. [8] The Rome III criteria classification system, also known as the only standardized symptom-based diagnostic criteria for functional gastrointestinal disorders (FGIDs), was used for recognizing the constipation. [1112] Patients with migraine who simultaneously suffered from constipation, those who signed the informed consent form, and those who were satisfied to participate in our study were divided into an experimental group and a control group.…”
Section: Methodsmentioning
confidence: 99%
“…It is likely that constipation plays a key role in starting a headache, or that headache and constipation have a common pathophysiology. [8] Constipation and migraines have common symptoms among which are pain and discomfort, which can lead to poor quality of life. Studies have shown that the prevalence of constipation in patients with primary headaches is higher than that of the normal population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After every reflux, there is a peristaltic wave in oesophagus which clears the gastric contents (16,33) . Almost 20% of adults complain of atleast 1 episode of heartburn/week and about 10% of them complain of daily episode of heartburn due to various trigerring factors mainly stress and sedentary lifestyle (8,14,45) .…”
Section: Discussion and Conclusion:-mentioning
confidence: 99%